The Effect of Teaching English Vocabulary Learning Strategies on Iraqi Intermediate School Students’ Vocabulary Performance and Reading Comprehension (Journal of the College of Languages (JCL), 2017)
The present study aims at empirically investigating the effect of vocabulary learning strategies on Iraqi intermediate school students’vocabulary performance and reading comprehension. The population of the present study includes all the 1st year male students of Al-Wark’a intermediate school of Al-Risafa 1/ General Directorate of Education for the first course of the academic year (2015-2016). To achieve the aim of the study ,a pre-test and post-test after (5) weeks of experiment are administrated .The sample of the present study consists of (100) subjects :(50) students as an experimental group and other (50) students as a control group . The subjects of both groups are equalized in these variables :pre-test, age, parents’ level of education , etc. After conducting the experiment , an achievement post- test has been applied to the two groups in order to find out the effect of teaching English vocabulary learning strategies on the sample’s vocabulary performance and reading comprehension .The results reveal that there are statistically significant differences between the experimental and control groups in their achievement in vocabulary and reading comprehension, in favour of the experiment group. In the light of the study results, conclusions, recommendations ,and suggestions for further studies are put forward.